The nature of our mistakes, from promise to practice: Water stewardship for sustainable hydropower in Sub‐Saharan Africa. (31st August 2021) - O'Brien, Gordon C.; Mor, Christoph; Buhl‐Nielsen, Eric; Dickens, Christopher W.S.; Olivier, Anton‐Louis; Cullis, James; Shrestha, Padmendra; Pitts, Hannah; Baleta, Hannah; Rea, Daniel
Abstract: The role of hydropower in the renewable energy mix for Africa's green development is widely recognised and underpinned by respective government and development partner funded initiatives. However, the growing demand for energy must be balanced with considerations for resource protection and benefit sharing of water resource developments with vulnerable human communities. An international conference on water stewardship for sustainable hydropower brought together key stakeholders in Nairobi, Kenya. This paper aims to synthesise the key messages of experts who attended the conference, presents the emerging body of good practice policies, plans and action in developing sustainable hydropower in Sub‐Saharan Africa, and provides recommendations for the way forward. Outcomes of the conference include considerations, planning for sustainable resource development, resource protection considerations, sharing of resource development benefits, and putting the promise into practice. This discussion describes the nature of our planning and management mistakes in the past, presents good practice options and how to implement sustainable hydropower in the future.